2020
DOI: 10.3762/bxiv.2020.60.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convenient Synthesis and Biological Evaluation of Bis(indolyl)methane Alkaloid and Bis(aryl)alkanes Derivatives with Anti-cancer Properties  

Abstract: An efficient and metal free methodology for the synthesis of bis(indolyl)methanes (BIMs) and bis(aryl)alkanes derivatives in the presence of B(C6F5)3 by the condensation of primary amines with pyruvates with good to high yields have been successfully developed. Some BIMs derivatives displayed good in vitro antitumor activity, screened by MTT assay. Compound 3b show the best anti-cancer activity against lung carcinoma cell A549 cells with IC50 of 4.52 µM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In light of the previously established biological activity of 3,3′- and 2,3′-bis­(indolyl)­methanes against a breast cancer cell line, ,,, a new series of synthetic marine sponge 2,3′-BIEA alkaloids, including protonated (±)-gelliusine E ( 4′ ), compound 6 , 6,6′-bis-(debromo)-gelliusine F ( 7 ), and analogues 15 , were accessed for their cytotoxicity against two breast adenocarcinoma cell lines, MCF-7 (estrogen receptor positive) and MDA-MB-231 (triple negative), as well as a monkey kidney non-cancerous cell line, Vero, by using the MTT assay (Table ). The results obtained indicated that substitution of the aryl moiety of the indole ring has an important role in the antiproliferative effect of 2,3′-BIEAs.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In light of the previously established biological activity of 3,3′- and 2,3′-bis­(indolyl)­methanes against a breast cancer cell line, ,,, a new series of synthetic marine sponge 2,3′-BIEA alkaloids, including protonated (±)-gelliusine E ( 4′ ), compound 6 , 6,6′-bis-(debromo)-gelliusine F ( 7 ), and analogues 15 , were accessed for their cytotoxicity against two breast adenocarcinoma cell lines, MCF-7 (estrogen receptor positive) and MDA-MB-231 (triple negative), as well as a monkey kidney non-cancerous cell line, Vero, by using the MTT assay (Table ). The results obtained indicated that substitution of the aryl moiety of the indole ring has an important role in the antiproliferative effect of 2,3′-BIEAs.…”
Section: Results and Discussionmentioning
confidence: 99%